(untitled) (The Spectrum, 2026)
This paper claims that alpine style mountaineering, undertaken as a solo exercise with minimal human support and no supplementary equipment, presents an instance of masculinity as performance. The study is based on the critical textual analysis of climber Reinhold Messner’s narrative Crystal Horizon (1989). For the purpose, the study aligns itself with Judith Butler’s assumption that gender constructs and manifests itself through performance (1988, 1999). Further, it borrows the ideas of the gradual construction and structural organization of Western masculinity, especially its essential and normative construction from R.W. Connell’s Masculinities (2005). The study examines masculinity in relation to three structural modalities: risk-perception, recognition and mediation of lack, and Oedipal consideration that perceives the mountain as a mother figure. The study demonstrates that alpine style mountaineering perpetuates the West’s essentialist conceptualization of masculinity as a risk-taking behavior, an identity position that enjoys negotiating the liminal space between life and death, and a dependent male that looks up to a mountain for spiritual and emotional refuge. Hence, masculinity in the context of alpine mountaineering is not always asserted through exemplary heroic standards; it is also asserted through performances that operate against vulnerability or a manifest lack or demonstrate dependence.